Combustion of fluoropolymer coated Al and Al–Mg alloy powders - Nie, Hongqi (2021)
This work presents an experimental investigation of the combustion characteristics of micron scale aluminum and aluminum-magnesium alloy powders coated with a thin layer of fluoropolymer. Burn times of the coated powders ignited by CO₂ laser were estimated from the time resolved emission signals recorded by photomultiplier tubes. Both fluoropolymer coated powders recorded reduced burn times. This result is likely associated with the lowered diffusion barrier in the fluoropolymer coated particles due to the gasification of oxide shell in the presence of fluorinated species from the decomposing fluoropolymer. Combustion temperatures determined using two-color pyrometry and optical spectroscopy were consistently higher for the fluoropolymer coated powders in comparison with that of the pristine. The reactivity of Al and Al-Mg alloy powders as assessed by constant volume explosion experiments was improved due to the fluoropolymer coating. Dust clouds of fluoropolymer-coated samples could achieve higher burning velocity as estimated from the experimental pressure traces using a semi-empirical correlation for dust explosions. A plausible mechanism responsible for the improvement in metal combustion due to the incorporation of fluoropolymer was proposed.